If it's not what You are looking for type in the equation solver your own equation and let us solve it.
22x-9+2x+16=
We move all terms to the left:
22x-9+2x+16-()=0
We add all the numbers together, and all the variables
24x=0
x=0/24
x=0
| f/4-15=15 | | 4x+6=-2(2x-5) | | -3y+48=4(y-2 | | 8z+7-5z=-24 | | 10y+8=4y+7 | | 12x-6=-4x-2 | | 18.26=3g+3.89 | | -16x–2=46 | | 7(5y-8)=29 | | 1−(2x+4)=−4x+5 | | 4(d-2)=4d | | -3(6d+8)=18+4d | | 16x-4=2x+14 | | 16-4=2x+14 | | -4x-37=-10x+53 | | -2v+9=3(-5v-6) | | 61=12x+8-2x | | h/3+9=27 | | 2(4x+5)=8x+10 | | w2+4w+12=228 | | 4000=p+(p)(0.09)(3) | | -34+6x=34+4x | | -3×+4=5x-7 | | -10=-4x–10 | | 9(1-5c)=-20 | | 2−2s=¾s+13 | | (4x-7)=(-2x+8) | | -14x-62=-10x+22 | | -16-6k=-9(8k-4) | | 3x+(2x-5x)=A)0 | | 3x+8=≤4 | | 4(x+7)=144 |